ANALISIS NILAI PERUSAHAAN SEKTOR BARANG KONSUMEN PRIMER DI BURSA EFEK INDONESIA - Yuliana Setyawati, (2022)
The purpose of this research is to find out and analyze whether the variables of debt policy, investment decisions and profitability on firm value. This research is included in quantitative research, where the object of this research is the primary consumer goods sector which is listed on the Indonesia Stock Exchange (IDX). This study uses a non-probability side with a purposive sampling method, with the resulting sample of 36 companies in the 2017-2020 period. This research uses the Panel Data Regression Model as the method assisted with E-views 12 program. The results of this research are: (1) there is no significant influence between the Debt Policy variable on Firm Value, (2) there is a significant influence between the Investment Decision variables on firm value, and (3) there is a significant influence between profitability variables on firm value.